The impact of career planning and development on improving employee performance in the General Authority for Applied Education and Training in the State of Kuwait - Makhseed, Haytham AbdulGafur (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to know the impact of planning and career development on the performance of employees of the Public Authority for Applied Education and Training in the State of Kuwait, and to highlight the extent of the impact of the concept of planning and development in order to understand the career path and its importance among employees. The descriptive analytical approach was applied, the researcher designed a questionnaire to collect the required data and work and it was analyzed through the use of the SPSS statistical analysis program, and the questionnaires were distributed to a sample The randomized study, which numbered (50) male and female employees, (46) copies were recovered, i.e. (92%) of the total sample. One of the most important findings of this study was that the level of work performance as evaluated by employees is low with a correlation between career planning and work performance, and the level of career planning is low according to the evaluation of employees of the Public Authority for Applied Education and Training, and there are no significant differences Statistical significance in the axes of career planning and work performance according to age, experience or training courses. The study concluded with a set of recommendations, including:* To pay attention and work to improve the job vacancy system in force in the Public Authority for Applied Education and Training in the State of Kuwait.* Urging employees to know the importance of applying career planning systems and raising awareness of their importance and the benefits that can be achieved for all, with the need to pay attention to motivational systems and methods.* The need to provide an adequate database for current and future career paths.* Encouragement to conduct more scientific research to reach the best methods to achieve an increase in the job performance of employees
Keywords: career planning; employee performance; career path; job design; development strategy; training